Qualidade de vida e sobrecarga de cuidadores de doentes crônicos após intervenção com dança de salão - Carvalho, Joselene Maria Mangueira (2015)
Caregivers of chronically ill patients change their habits to care of the patient who needs care, but often fails to maintain their own health. Objective: To analyze changes in the quality of life and burden arising from the physical activity in caregivers of chronic patients. Methods: In this study we performed a field research with the use of twice a week ballroom dance classes in 16 caregivers of patients of chemotherapy and base Hospital hemodialysis São José do Rio Preto - SP. To evaluate the quality of life we used the Quality of life Questionnaire World Health Organization - WHOQOL - BREF and to evaluate the burden we used the Zarit scale and a semi-structured interview. Results: Positive changes were found in the perception of individuals in reports and interview after the intervention. Conclusion: Physical activity can be a resource used for the improvement of Caregivers of health indicators.